(untitled) (Eurasian Journal of Engineering and Technology, 2022)
Copolymers based on quinozolindione-2,4 acrylate and acrylic monomers were synthesized. The IR spectra of the obtained polymer products were studied. When they were added to diesel fuel, it was observed that the physico-chemical properties of diesel fuel improved.